Fatal Lodderomyces elongisporus Fungaemia in COVID-19 Patient - Zainuddin, Nurnabilah; Zainol Abidin, Nor Zanariah; Tengku Jamaluddin, Tengku Zetty Maztura; Masri, Siti Norbaya (Universiti Putra Malaysia, 2023)
Lodderomyces elongisporus, an ascomycetous yeast, is often misidentified as Candida parapsilosis due to its physiologic similarity. Compared to Candida parapsilosis complex, L. elongisporus is still inferior in regard to incidence and virulence. We report a case of L. elongisporus fungaemia in a patient with diabetic ketoacidosis (DKA) precipitated by COVID-19 category 5 infection. A 52-year-old diabetic and hypertensive lady was brought in for fever, cough and lethargy for four days, with sudden onset of dyspnoea. Upon arrival, she was febrile, and in metabolic ketoacidosis. Her lung auscultation was clear. SARS-CoV-2 RNA was detected via real-time polymerase chain reaction (RT-PCR). Her blood culture grew L. elongisporus, identified via matrix-assisted laser desorption/ionization time of flight (MALDI-TOF). Although treated with intravenous (IV) amphotericin B for four days, she succumbed on the sixth day of admission. Accurate identification of this yeast, especially in differentiating it with Candida parapsilosis complex, remains a diagnostic challenge for routine diagnostic laboratories. MALDI-TOF offers a reliable alternative for accurate and prompt diagnosis. Co-infections with COVID-19 have never been recorded worldwide. We highlight the first case of L. elongisporus isolation co-existing with SARS-CoV-2 infection during this pandemic.